Calciphylaxis in catastrophic antiphospholipid antibody syndrome. Issue 4 (June 2015) - Shah, Surbhi; Larson, Andrew; Datta, Yvonne
Abstract : Antiphospholipid antibody syndrome (APS) is a multisystem disorder characterized by vascular thrombosis and presence of circulating autoantibodies. The presence of APS can predispose to macrovascular as well as microvascular thrombotic events. Renal involvement is a common occurrence especially in the background of systemic lupus erythematosus. Skin appears to be another frequent target organ and a significant proportion of patients may present with skin lesions at the time of diagnosis. We present the case of a patient who presented with skin necrosis secondary to antiphospholipid antibody syndrome despite being on therapeutic anticoagulation and then developed dystrophic calcification secondary to her renal insufficiency. This complex skin condition eventually leads to her demise, as she was not a candidate for surgical management of these lesions. Why is this important? This case brings to our attention the need to consider calciphylaxis as a cause of ecchymotic-appearing skin lesions in dialysis patients on warfarin in patients with antiphospholipid antibody syndrome.